Clinical blood analysis of the great tit Parus major - Maria Drahulian (ScienceRise, 2018)
The blood analysis of the great tit in a protected area of National Nature Park “Homilshanski Forests” (Kharkiv Region, Ukraine) was performed in the age-related dynamics of its postembryogenesis. Using our own method, developed for collecting venous blood from the eye sinus, the identity of leukogram percentages between the literary data and our obtained results was established thereby providing evidence in favour of the application of our development. Erythrocytes were studied with the help of the micronucleus test, which results reliably testify that the studied birds were not exposed to any chemical or physical contamination. No parasitic infections were found in blood smears. Further improvement of the blood taking method is planned in order to collect samples for biochemical and genetic analyses